1980
DOI: 10.1128/aem.40.1.19-24.1980
|View full text |Cite
|
Sign up to set email alerts
|

Production of l -Glutamine by a Penicillin-Resistant Mutant of Flavobacterium rigense

Abstract: To establish a practical method for the fermentative production of l -glutamine, cultural conditions for the accumulation of a large amounts of l -glutamine were investigated by using Flavobacterium rigense 703, which was previously reported by us as a l -glutamine-producing mutant. As a result, a yield of 25 mg of l -glutamine per ml was obtained after a 48-h cultivation in a medium containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…As described in previous papers (6,7), we found that a penicillin-resistant mutant of Flavobacterium rigense, strain 703, produces 25 g of L-glutamine per liter in a culture medium containing mainly 5% glucose and 7% (NH4)2fumarate. The existence of 0.9 to 1.6% ammonia and 5.5% fumaric acid in a medium is essential for the accumulation of large amounts of L-glutamine.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…As described in previous papers (6,7), we found that a penicillin-resistant mutant of Flavobacterium rigense, strain 703, produces 25 g of L-glutamine per liter in a culture medium containing mainly 5% glucose and 7% (NH4)2fumarate. The existence of 0.9 to 1.6% ammonia and 5.5% fumaric acid in a medium is essential for the accumulation of large amounts of L-glutamine.…”
supporting
confidence: 72%
“…3556) (17) were used. The conditions for stock culture were described previously (6). L-Glutamine production medium (basal medium) contained 5% glucose, 1.5% yeast extract, 7% (NH4)2-fumarate, 0.1% KH2PO4, 0.1% K2HPO4, 0.05% MgSO4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutamine is one of the most important compounds in nitrogen metabolism; it is not only a constituent of proteins but is also a donor of the amino (amido) moiety in the biosynthesis of other amino acids, purines, pyrimidines, pyridine coenzymes, and complex carbohydrates. Glutamine is also used in the treatment of gastric ulcers and has been produced commercially by direct fermentation with certain bacteria (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%